The products of the garden for life and health (2014)
This article was written by the author from the knowledge of her parents, of the Nonuya and Muinane groups of the Middle Caquetá River (Colombian Amazon), with the support of an indigenous research grant of the Tropenbos-Colombia Foundation. The article stresses the importance and meaning of the garden for indigenous peoples, and explains how the gardens in former times were, the labors involved in the preparation of a new garden (clearing the underbrush, slashing, burning, planting and maintenance), the manner of planting different species, the species and varieties of seeds planted, the changes that have taken place in the gardens nowadays, and the process to extract manioc starch and to prepare the yellow manioc, used to obtain fariña (thick manioc flour). It includes a glossary with the biological identification of plants and animals and the explanation of terms and expressions in the Muinane language and local Spanish.